In ViVo anti-malarial activity of some Malaysian traditional plants: Community's awareness and ethnobotanical survey / Abdulelah Hussien Ahmed Al-Adhroey - Abdulelah Hussien, Ahmed Al-Adhroey (2011)
In Malaysia, located in the hot, humid equatorial region, malaria stills an important public health issue among rural and aboriginal people. In parallel with the implementation of Malaysia's malaria elimination programme, this cross-sectional was carried out among 223 households from forest-aboriginal and rural areas, Lipis district, Pahang state, to investigate the awareness of the communities regarding malaria: knowledge, attitudes and practices (KAP) and to establish a preliminary ethnobotanical database for the plants traditionally used to treat malaria. The in vivo anti-malarial activity of the methanol extracts of Cocos nucifera, Labisia pumila, Languas galanga and Piper betle selected based on the ethnobotanical survey were evaluated against the laboratory malaria model Plasmodium berghei. The acute oral toxicity (LD50) was determined to ascertain the safety of the extracts. The phytochemical and antioxidant potentials of the crude extracts were also investigated to elucidate the possibilities of its anti-malarial effects. The rural population has shown a higher knowledge about the transmission of the disease (aboriginal 50%, rural 70.7%, P<0.01). However, the aboriginal participants showed higher practices in the use of medicinal plants and belief in witchcraft (P < 0.05, P < 0.01, respectively). On the other hand, the two communities did not show significant differences in their knowledge, attitudes and practices about the symptoms of malaria, severity of the disease and the use of mosquito bed nets, respectively. Nineteen species belonging to 17 families were identified. Twelve plant species have not previously been documented for the treatment of malaria in Peninsular Malaysia. The results of anti-malarial activity of C. nucifera, L. pumila, L. galanga and P. betle showed significant (P < 0.05) results during the early, established and residual P. berghei infections in mice. Overall results of the in vivo anti-malarial activity of the methanol extract of the plants during early, established and residual malaria infections with evidence of increasing mean survival time of the infected mice showed that P. iii betle and L. galanga were the most effective followed by C. nucifera and L. pumila, respectively. The present study showed that the test extracts are toxicologically safe by oral administration. Phytochemical screening of the methanol extracts of the plants revealed the presence of alkaloids, terpenoids, anthraquinones, flavonoids, tannins, saponins, glycosides and steroids. At a concentration of 25 μg/mL P. betle showed potent DPPH scavenging antioxidant activity % (80.68%) followed by L. pumila (40.66%) and L. galanga (37.88%) where as C. nucifera exhibited a weak DPPH scavenging activity (5.52%). In conclusion, the aboriginal and rural communities showed awareness regarding malaria as a disease; however their KAP were inadequate, in particular, among the aboriginal population. Providing efficient health education to people residing in malaria endemic areas would improve their understanding about malaria prevention in order to bring about the elimination of malaria from the country. The ethnobotanical findings can be used as an ethnopharmacological basis for selecting plants for further anti-malarial phytochemical and pharmaceutical studies. The anti-malarial activity observed in this study also confirms that the Malaysian folkloric medicinal application of these plants has a pharmacological basis.